High‐Rate and Large‐Capacity Lithium Metal Anode Enabled by Volume Conformal and Self‐Healable Composite Polymer Electrolyte - Shuixin Xia; Jeffrey Lopez; Chao Liang; Zhichu Zhang; Zhenan Bao; Yi Cui; Wei Liu (Advanced Science, 2019)
Abstract The widespread implementation of lithium‐metal batteries (LMBs) with Li metal anodes of high energy density has long been prevented due to the safety concern of dendrite‐related failure. Here a solid–liquid hybrid electrolyte consisting of composite polymer electrolyte (CPE) soaked with liquid electrolyte is reported. The CPE membrane composes of self‐healing polymer and Li+‐conducting nanoparticles. The electrodeposited lithium metal in a uniform, smooth, and dense behavior is achieved using a hybrid electrolyte, rather than dendritic and pulverized structure for a conventional separator. The Li foil symmetric cells can deliver remarkable cycling performance at ultrahigh current density up to 20 mA cm−2 with an extremely low voltage hysteresis over 1500 cycles. A large areal capacity of 10 mAh cm−2 at 10 mA cm−2 could also be obtained. Furthermore, the Li|Li4Ti5O12 cells based on the hybrid electrolyte achieve a higher specific capacity and longer cycling life than those using conventional separators. The superior performances are mainly attributed to strong adhesion, volume conformity, and self‐healing functionality of CPE, providing a novel approach and a significant step toward cost‐effective and large‐scalable LMBs.